Avaliação das capacidades organizacional e operacional de um banco para a coprodução de serviços de telecomunicações de dados - Rech, Carlos Henrique Benevenuto (Universidade do Vale do Rio dos Sinos, 2014)
This work analyzed the organizational and operational capabilities of a bank for co-production of data telecommunications services. The construct ability to co-produce telecommunication services has been operationalized through the measurement of eight dimensions forming organizational and operational capabilities of service co-production, developed in previous exploratory study of Teixeira (2010) and expanded later by study developed by Przyczynski (2013). Seeking to expand the studies developed by the authors, a large financial institution in Brazil has been selected in order to apply the survey instrument to a final sample of 299 branches. Statistical results show that 6 constructs are responsible for 27.8% of service failure. Results also suggest that the constructs Functional Training, Facilities Management and Equipment Management exerts greater influence on Perception of Failure, followed by Strategic Planning and, finally, Security. As for significance, Functional Training was highly significant, followed by Equipment Management and Equipment Facilities.
Keywords: Banco; Coprodução de serviços; Capacidades operacionais; Capacidades organizacionais; Instituição financeira; Bank; Co-production of services; Operational capacities; Organizational capabilities; Financial institution; ACCNPQ::Ciências Sociais Aplicadas::Administração